Brief research report: development of codes of conduct in online classrooms for Vietnamese high school students - Thanh Thuy, Bui; Nguyen, Xuan-An; Thi Viet Ha, Nguyen; Thanh Ha, Vo; Thi Kieu Anh, Nguyen; Thi Ngoc Hien, Do (Frontiers in Education, 2025)
BackgroundIn today's digital age, online education helps eliminate certain barriers faced by traditional education, however, it also presents challenges, including issues related to the culture of conduct among high school students in their relationships with instructors and peers. Therefore, developing Codes of Conduct in Online Classrooms is necessary to create a healthy, fair, and engaging learning environment.MethodA procedure consisting of three stages is used, namely: (1) Item generation; (2) Theoretical analysis; and (3) Psychometric analysis. This study involved surveys of 923 participants, including 321 teachers and 602 students from high schools in Vietnam. One of the outcomes of this research is a dataset comprising six files related to the scale development process. From the collected data, we conducted analyses to explore the Codes of Conduct in Online Classrooms of Vietnamese High School Students using Exploratory Factor Analysis and Confirmatory Factor Analysis.ResultsThe analysis results indicate that the Codes of Conduct in Online Classrooms of Vietnamese High School Students include four aspects: (1) Students' attitudes toward teachers and classmates; (2) Students' communication conduct toward teachers and classmates; (3) Students' conduct in using the camera; and (4) Dress Code, Sitting Posture and Learning Location Regulations.ConclusionThe codes of conduct in online classrooms play a crucial role in creating a positive, effective, and culturally rich learning environment. This article partially contributes to establishing fundamental guidelines on the conduct of high school students in online classes, thus providing an important foundation for forming appropriate behavior between all stakeholders.